2004
DOI: 10.4049/jimmunol.173.2.1266
|View full text |Cite
|
Sign up to set email alerts
|

Type I IFN Protects Permissive Macrophages fromLegionella pneumophilaInfection through an IFN-γ-Independent Pathway

Abstract: Legionella pneumophila is an intracellular pathogen whose replication in macrophages is mainly controlled by IFN-γ. Freshly isolated peritoneal macrophages elicited in vivo with thioglycolate (TG) from A/J mice are highly permissive to L. pneumophila growth in vitro, while TG-elicited macrophages from CD1 mice are resistant. In this study, we show that when CD1 TG-macrophages are cultured for 7 days, they become permissive to Legionella infection. We demonstrate that treatment with type I IFN (IFN-αβ) totally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 52 publications
6
48
1
Order By: Relevance
“…IL-12p40 secretion from the infected macrophages was similar at all time points in both infection groups. Schiavoni et al (31) reported that aged C57BL/6 macrophages are equally permissive for the intracellular growth of Legionella as fresh A/J macrophages, because of their reduced production of type I IFNs. However, we found no difference in the production of type I IFNs in C57BL/6 macrophages regardless of the infective strain, contradicting the contribution of type I IFNs on restriction of Legionella replication in infected macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-12p40 secretion from the infected macrophages was similar at all time points in both infection groups. Schiavoni et al (31) reported that aged C57BL/6 macrophages are equally permissive for the intracellular growth of Legionella as fresh A/J macrophages, because of their reduced production of type I IFNs. However, we found no difference in the production of type I IFNs in C57BL/6 macrophages regardless of the infective strain, contradicting the contribution of type I IFNs on restriction of Legionella replication in infected macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…IL-12p40 was produced at significant level and there was no difference in the amounts of IL-12p40 produced by macrophages infected with the flaA mutant bacteria compared to those cells infected with the parent Corby strain (data not shown). Recent work revealed that type I IFNs is important for resistance to Legionella infection in murine macrophages (31). Therefore, IFN-α and -β were determined in supernatant of either the parental strain or the flaA mutant infected macrophages, which revealed that type 1 IFNs production was minimal (data not shown).…”
Section: Production Of Il-12p40 and Type 1 Interferon By Infected Macmentioning
confidence: 99%
“…On the other hand, full innate intracellular resistance to L. pneumophila (and certainly other intracellular bacteria) depends on many additional mechanisms such as types I and II IFN-as well as TNF-␣-mediated effects, and perhaps also on Nramp1, antimicrobial peptides, or immunity-related GTPases (13,15,(45)(46)(47)(48)(49)(50). It might thus be conceivable that in case of L. pneumophila infection, one of these last mentioned resistance mechanisms is less functional in human cells compared with mice resulting in an overall stronger replication of Legionella in human cells compared with, for example, C57BL/6 macrophages despite functional hNAIP and hIpaf.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on Legionella pneumonphila (11), Salmonella typhimurium (12), Shigella flexneri (13), Bacillus anthrasis (14) and Mycobacterium bovis bacillus Calmette-Guérin (15) showed that IFNIs are protective for host, at least partially through enhancing IFN-␥/NO production and suppressing bacterial invasion. In contrast, some studies have shown that IFNIs are detrimental, especially in certain bacterial infections.…”
Section: T He Group Of Type I Ifns (Ifnis)mentioning
confidence: 99%